A coupled thermo-mechanical discontinuum model for simulating rock cracking induced by temperature stresses. (June 2015) - Jiao, Yu-Yong; Zhang, Xiu-Li; Zhang, Huan-Qiang; Li, Hai-Bo; Yang, Sheng-Qi; Li, Jian-Chun
Abstract: Temperature change often induces thermal stresses in brittle materials, such as rock, causing cracking and hazardous accidents under certain circumstances. Within the framework of the discontinuous deformation analysis (DDA) method, this paper presents a coupled thermo-mechanical discontinuum model for simulating the rock cracking process induced by temperature stresses. Firstly, based on the energy conservation principle, heat transfer process in the block system is analyzed to determine changes in the temperature field; secondly, thermal stresses are calculated and coupled with the original stress field by applying the theory of thermoelasticity; thirdly, the interface between any two adjacent blocks is checked with two failure criteria to determine whether cracking occurs; fourthly, the proposed model is incorporated into a DDA-based program for failure analysis; finally, several numerical experiments are performed for verification, the simulated results agree well with the existing analytical and test results, indicating that the proposed approach is effective for thermal cracking simulation.